Teknologi Pengemasan Desain dan Pelabelan Kemasan Produk Makanan Desa Kalisalak Kecamatan Kedungbanteng Kabupaten Banyumas (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract Packaging is a process of wrapping, container or packaging of a product using certain materials so that the product inside can be accommodated and protected. Product packaging is part of the packaging of a product, one way to preserve or extend the life of the food or food products contained therein. Packaging technology continues to develop from time to time, from simple/traditional packaging processes using natural materials such as leaves or woven bamboo to modern technologies such as today, traditional packaging such as making tempeh with banana leaves or teak leaves, wrapping palm sugar with coconut leaves. or dry banana leaves. Packaging technology that is increasingly advanced and modern has almost eliminated the use of traditional packaging materials such as plastic, cans/metal, composite paper, and so on. Packaging is one of the factors that is very important and absolutely necessary in today's competitive business world. This is very important because of its function and use in improving product quality and selling power of the product. Product packaging and labels besides functioning as product security contained in it also function as promotional media and information about the product concerned. Good and attractive product packaging will provide its own value as an attraction for consumers, especially Micro, Small and Medium Enterprises. Problems regarding product packaging and labels sometimes become obstacles for the development or progress of a business. Many problems arise when a business wants to have a product packaging that is good quality and meets existing national standards.